Survey

* Your assessment is very important for improving the work of artificial intelligence, which forms the content of this project

Document related concepts

Gröbner basis wikipedia, lookup

Linear algebra wikipedia, lookup

Equation wikipedia, lookup

Birkhoff's representation theorem wikipedia, lookup

System of polynomial equations wikipedia, lookup

Dual space wikipedia, lookup

Factorization of polynomials over finite fields wikipedia, lookup

Homological algebra wikipedia, lookup

Laws of Form wikipedia, lookup

Complexification (Lie group) wikipedia, lookup

Deligne–Lusztig theory wikipedia, lookup

Tensor product of modules wikipedia, lookup

Eisenstein's criterion wikipedia, lookup

Polynomial ring wikipedia, lookup

Fundamental theorem of algebra wikipedia, lookup

Basis (linear algebra) wikipedia, lookup

Commutative ring wikipedia, lookup

Transcript
```Solutions to Homework 9
46. (Dummit-Foote 10.3 #2) Suppose Rn ' Rm . Let I be a maximal ideal of R, then Rn /IRn '
Rm /IRm . By the exercise 12 of section 2, this implies that (R/I)n ' (R/I)m , and as these are
vector spaces over the field R/I, we have n = m.
47. (a) Suppose that Q were a free Z-module. Let a/b, c/d ∈ Q. Then bc(a/b) + (−ad)(c/d) = 0,
which says that there is a non-trivial linear relation between any two basis elements of Q. Hence
Q is a free Z-module of rank at most 1. But a/2b is not in the Z-span of a/b for any a/b ∈ Q,
which says that Q cannot have rank 1 either. Thus Q is not a free Z-module.
(b) Suppose that I were a free R-module. If f and g are basis elements, then the non-trivial
relation −gf + f g = 0 forces I to have rank at most 1. Thus I = Rf for some f , but this implies
that I is a principal ideal.
To see that I cannot be principal, suppose we had (X, Y ) = I = (f ). Then there exist g, h ∈ R
such that gf = X, hf = Y . The first equation says that the Y -degree of f (the degree of f when
viewed as a polynomial in Y with coefficients in F [X]) must be zero. Similarly, the X-degree of
f must be zero by the second equation. But this implies that f is a constant and thus I = R, a
48. (a) (Dummit-Foote 10.3 #11) Let φ : M1 → M2 be a non-zero R-module homomorphism. Since
M1 is irreducible, we have ker(φ) = 0. Since M2 is irreducible, we have im(φ) = M2 . Therefore
φ is injective and surjective, and hence an isomorphism. If M1 = M = M2 , then we have shown
that every element of EndR (M ) is an isomorphism. In particular, every element of EndR (M ) has
an inverse with respect to composition, which proves that EndR (M ) is a division ring.
(b) Since M is a simple R-module, we have M = Rm for some m ∈ M (if m 6= 0 then Rm is a
submodule of M and thus must be all of M ). Then for any R-module homomorphism φ : M → M ,
we have φ(m) = rm for some r ∈ R, and this formula completely determines φ. Let ψ ∈ EndR (M )
be another endomorphism of M , and suppose that ψ(m) = sm. Then
φ(ψ(m)) = φ(sm) = sφ(m) = srm = rsm = rψ(m) = ψ(rm) = ψ(φ(m))
which shows that EndR (M ) is commutative. By part (a), it is a division ring, and thus a field.
49. Let N be a submodule of M , and let S = {Ni } be the set of all finitely generated submodules
of N . By assumption, S has a maximal element, call it N 0 . Then for any Ni ∈ S, we have Ni ⊂ N 0 .
If this were not the case, then we could pick x ∈ Ni , x ∈
/ N 0 . The submodule N 0 + Rx would
be a finitely generated submodule properly containing N 0 , contradicting the maximality of N 0 .
Therefore,
[
N=
Ni ⊂ N 0 ⊂ N
i
N 0.
which says that N =
that M is Noetherian.
We conclude that every submodule of M is finitely generated, which says
1
50. (a) The chain
· · · ker(un ) ⊆ ker(un+1 ) ⊆ ker(un+2 ) · · ·
of submodules of M must terminate by the Noetherian assumption. So pick n such that ker(un ) =
ker(un+1 ). Let m ∈ ker(u). The maps uk are all surjective by the surjectivity of u. Pick x ∈ M
such that un (x) = m. Applying u, we get the equation
un+1 (x) = u(m) = 0
which says that x ∈ ker(un+1 ) = ker(un ). This implies that m = 0, and hence u is injective.
(b) The chain
· · · im(un ) ⊇ im(un+1 ) ⊇ im(un+2 ) ⊇ · · ·
of submodules must terminate by the Artinian condition. So pick n such that im(un ) = im(un+1 ).
Let m ∈ M . We can find an x ∈ M such that un (m) = un+1 (x). Then un (m − u(x)) = 0, but un
is injective because u is injective. Hence m = u(x), and it follows that u is surjective and thus an
isomorphism.
51. Let {ei } be a basis of V , indexed by Z. We define a map R ⊕ R → R, by sending (1, 0) 7→ f ,
and (0, 1) 7→ g, where f (e2i ) = ei and f (e2i−1 ) = 0, and g(e2i ) = 0 and g(e2i−1 ) = ei . We extend
the map by R-linearity to get an R-module map. Note that 1 here really means idV . Checking
surjectivity and injectivity is straightforward, and thus our map is an isomorphism.
2
```
Related documents